The Investment Concept of Sharia Insurance According to National Sharia Council and Its Regulation in Indonesia - LUTH, Thohir; BURHANUDDIN, BURHANUDDIN; SANTOSO, Budi (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017DO - 10.14505/jarle.v8.7(29).18, 2017)
It is a fact that contemporary Islamic scholars have different  opinion related to  legalization of insurance (ta’mîn). The differences indicate there is a plurality in Islamic legal thought in responding contemporary issues which dynamic along with the change of time. This article is aimed to analysis the investmen concept of  sharia insurance explained  on dictum (fatwa) National Sharia Council  (NSC) and its regulations which legitimize  those  enforcement. This discussion is important ‘to introduce the new concept of investing in the insurance  products which later has caused controversy from the aspect of validity. The methods used to write this article is critical content analysis by making the NSC’s fatwa and the regulation of sharia insurance  as its object, so both of which  can be found the excellence and weakness of the concepts offered.  The interesting of this concept is that the investment  can be incorporated  with insurance products, so that participants who pay a premium not only get guaranty  indemnity of risk but  also entitled to get a profit sharing of their fund investment.  As for the weakness of this concept is the  using of hybrid contract which  tends to  imposed to fullfil pragmatism needs, so that has opened new scientific debate from side of validity.